Interpreting patterns in transcriptomes and ancient DNA from Next Generation Sequencing data - Lin, AT (2019)
A goal of biological research is to understand the implications of the evolutionary process. Efforts using direct analysis of nucleotide sequences have had a tremendous impact in achieving this goal. The revolution in palaeogenomics and transcriptomics research over the past decade is inextricably intertwined with the power of next generation sequencing platforms and the ability to target and sequence short DNA molecules at a high resolution. In palaeogenomics, archaeological specimens that were previously unsuitable for DNA analyses due to extensive postmortem sequence damage can now be used successfully as source material. The increasing availability of ancient DNA allows for greater precision and accuracy in the molecular dating of phylogenetic trees, and provides invaluable insights into the timing, location, mechanisms, and dynamics of important evolutionary processes such as domestication. In gene expression data, the sensitivity of RNA-seq allows for the potential detection of alternative splice isoforms of transcripts as well as rare and context-specific transcripts, such as those seen in complex tumour environments. In this thesis, I use bioinformatic techniques to 1) evaluate the expression of endogenous retrovirus-encoded putative oncogenes np9 and rec in RNA-seq data, and find that these gene products are upregulated in many cancers, and in specific stages of early embryonic development; 2) find that np9 and rec are positively and negatively correlated with the upregulation and downregulation of many cancer stem cell and epithelial-mesenchymal transition biomarkers; 3) utilise ancient and modern animal mitochondrial genomes to find evidence of time-dependence evolutionary rate estimates, showing that the degree of this effect varies among parts of the mitochondrial genome and with the estimation method being used; 4) reconstruct early animal domestication processes of pigs in Europe.